Lsolated acetabular revisions of articular surface replacement (ASR) XL implants with highly porous titanium cups and Delta bearings. Issue 2 (March 2021) - Castagnini, Francesco; Mariotti, Federica; Tassinari, Enrico; Bordini, Barbara; Zuccheri, Federica; Traina, Francesco
Introduction: Articular surface replacement (ASR) XL implants exhibit higher-than-expected revision rates, blood ion concentrations and soft tissue lesions, making revisions troublesome and potentially unsatisfying. Appropriate techniques and outcomes in ASR XL revisions are rarely documented. The aims of this study were the assessments of pre-revision data, post-revision clinical and radiographic outcomes and ion levels in isolated acetabular ASR XL revisions performed using highly porous titanium cups and Delta ceramic articulations. Methods: 18 isolated acetabular ASR XL revisions in 16 patients were performed using Ti-Por cups (Adler Ortho, Milan, Italy) and Delta bearings (CeramTec, Plochingen, Germany). Pre-revision demographic, clinical, radiological and implant-related features were assessed. Clinical and radiographic parameters (cup positioning, osseointegration) after revisions were evaluated at a minimum follow-up of 5 years. Ion concentrations in blood and urine were collected in pre-revision setting and 1 year after revision. Results: 4 complications occurred in 3 different revisions (16.7%), 1 dislocation, 2 infections, 1 psoas impingement. No re-revision was performed at 5 years (1 scheduled arthroscopy). Good clinical outcomes were achieved (HHS score: 88.3 ± 9.2). All the cups showed reassuring signs of osseointegration (>3 parameters). Blood ion concentrations significantly decreased: patients with Co blood ion concentration over the threshold (7 μg/l) decreased from 76.5% to 0%. No pre-revision or intraoperative data influenced the revision outcomes. Conclusions: Highly porous titanium cups and Delta ceramic articulations provided reliable mid-term clinical and radiographic outcomes in isolated acetabular ASR XL revisions. Ion concentrations significantly decreased. Multicentre prospective controlled studies are required to confirm these preliminary outcomes.